2006
DOI: 10.1111/j.1525-1497.2006.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Nutrition and weight loss information in a popular diet book: Is it fact, fiction, or something in between?

Abstract: BACKGROUND/OBJECTIVE: Diet books dominate the New York Times Advice Best Seller list and consumers cite such books as an important source of nutrition information. However, the scientific support for nutrition claims presented as fact (nutrition facts) in diet books is not known. DESIGN/MEASUREMENTS: We assessed the quality of nutrition facts in the best‐selling South Beach Diet using support in peer‐reviewed literature as a measure of quality. We performed structured literature searches on nutrition facts l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Another previous study evaluated nutrition facts presented in a single best-selling book by searching peer-reviewed literature that would or would not support the facts (41) . The study found that only one-third of the nutrition facts was supported by peer-reviewed literature (41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another previous study evaluated nutrition facts presented in a single best-selling book by searching peer-reviewed literature that would or would not support the facts (41) . The study found that only one-third of the nutrition facts was supported by peer-reviewed literature (41) .…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study evaluated nutrition facts presented in a single best-selling book by searching peer-reviewed literature that would or would not support the facts (41) . The study found that only one-third of the nutrition facts was supported by peer-reviewed literature (41) . Although this previous and our present study differ in focus and the number of books examined, both suggest that nutritional information provided in popular US books is not necessarily based on scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The Zone diet includes a mild reduction in carbohydrate intake to 40% of total macronutrient intake, and a mild increase of protein and fat intake to 30% each of the total nutritional intake per day. The South Beach diet, a more recent approach, is a fiber-rich diet that promotes intake of complex carbs, or so-called good carbs, from various sources such as fruits, vegetables, whole grains, and beans, while avoiding simple or "bad" carbs, represented by sugar and industrial syrups and sweeteners [10,[16][17][18]. An extreme modification of a LC diet, the ketogenic or "keto" diet, induces a nutritional ketosis and thus production of ketone bodies from fat tissue in the body, by increasing energy intake from fat, and significant restriction of carbohydrate intake to 20-50 g per day and subsequent glycogen storages' depletion.…”
Section: Low Carbohydrate (Lc) Dietmentioning
confidence: 99%
“…These differences are what receive the overwhelming preponderance of attention in diet books, the media, and from the food industry, resulting in conflicting messages. 47,48 The US weight loss market in 2014 was valued at US$59.8 billion, a portion of which is derived from diet book sales. 49 Thousands of diet books are published by scientists and researchers every year, each with the potential to exert influence over public perceptions.…”
mentioning
confidence: 99%
“…These differences are what receive the overwhelming preponderance of attention in diet books, the media, and from the food industry, resulting in conflicting messages. 47,48…”
mentioning
confidence: 99%